Understanding the transfer student experience using design thinking. Issue 2 (12th June 2017) - Whang, Linda; Tawatao, Christine; Danneker, John; Belanger, Jackie; Edward Weber, Stephen; Garcia, Linda; Klaus, Amelia
Abstract : Purpose: This paper aims to discuss a 2015-2016 University of Washington Libraries project focused on understanding the needs and challenges of transfer students on the Seattle campus and developing innovative ways to support transfer student success. Design/methodology/approach: The study uses design thinking methods, including interviews and rapid iterative prototyping and feedback, to understand and emphasize the user experience. Findings: Transfer students at the Seattle campus identify themselves as a unique group separate from other undergraduates because of their prior experience, shortened timeline at the university and their need to balance academic, work and family commitments. Because transfer students often have little time to learn about and effectively use campus resources, the authors found that working with campus partners to enrich transfer-specific student orientations and events with educational and practical content was the most effective means of supporting new students. Research limitations/implications: This pilot study was conducted over an 11-month period with a small number of participants, but the iterative nature of design thinking allowed the authors to gather new feedback from a variety of students and staff at each phase. Originality/value: This study showcases how design thinking methods can increase understanding of transfer student and other user needs. The design thinking approach can also enable the rapid development of library and campus services, as well as outreach efforts, to meet user needs.